Interaction between the New World begomovirus Euphorbia yellow mosaic virus and its associated alphasatellite: effects on infection and transmission by the whitefly Bemisia tabaci - Mar, Talita Bernardon; Mendes, Igor Rodrigues; Lau, Douglas; Fiallo-Olivé, Elvira; Navas-Castillo, Jesús; Alves, Murilo Siqueira; Murilo Zerbini, F (Journal of general virology, 2017)
The majority of Old World monopartite begomoviruses (family Geminiviridae) are associated with satellite DNAs. Alphasatellites are capable of autonomous replication, but depend on the helper virus for movement, encapsidation and transmission by the insect vector. Recently, Euphorbia yellow mosaic alphasatellite (EuYMA) was found in association with Euphorbia yellow mosaic virus (EuYMV) infecting Euphorbia heterophylla plants in Brazil. The geographical range of EuYMA was assessed in a representative sampling of E. heterophylla plants collected in several states of Brazil from 2009 to 2014. Infectious clones were generated and used to assess the phenotype of viral infection in the presence or absence of the alphasatellite in tomato, E. heterophylla, Nicotiana benthamiana, Arabidopsis thaliana and Crotalaria juncea. Phenotypic differences of EuYMV infection in the presence or absence of EuYMA were observed in A. thaliana, N. benthamiana and E. heterophylla. Symptoms were more severe when EuYMV was inoculated in combination with EuYMA in N. benthamiana and E. heterophylla, and the presence of the alphasatellite was determinant for symptom development in A. thaliana. Quantification of EuYMV and EuYMA indicated that EuYMA affects the accumulation of EuYMV during infection on a host-dependent basis. Transmission assays indicated that EuYMA negatively affects the transmission of EuYMV by Bemisia tabaci MEAM1. Together, these results indicate that EuYMA is capable of modulating symptoms, viral accumulation and whitefly transmission of EuYMV, potentially interfering with virus dissemination in the field.